SENSITIVITY ANALYSIS OF PRECIPITATION AND RUNOFF PARAMETER TO ASSESS NEMO/INDO12 MODEL OUTPUT - Priyono, Bayu; Berlianti, Desy (JFMR (Journal of Fisheries and Marine Research), 2021)
We investigate the sensitivity of precipitation and runoff parameters to a set of NEMO/INDO12 scenarios. A series of simulations are imposed based on reduction rate of each precipitation and runoff parameter to examine its influences to the main ocean characteristics behavior (temperature and salinity). One-set evaluates of two different simulations by using normal and reduce precipitation rate on whole domain Indonesian Sea Water, and the other-set evaluates of two simulations which focusing the experiment by reduce precipitation and runoff rate only on South China Sea region. Our results elucidate the complexity of the relationship between the varied of precipitation and runoff reduction rate, showing that the control of precipitation and runoff rate produced significant impacts on salinity profile up to subsurface stratification. Additionally, the reduction rate of precipitation and runoff indicated that the temperature changes do not always response significantly.